Валентнocть существительных со значением “совокyпность множества” в современном английском языке - Астраускайте, Даля (Kalbotyra, 1987)
The aim of the present article is to investigate valency of nouns with the meaning of integral multitude in present-day English (assemblage, batch, collection, etc.). It is suggested that notion of valency refers to two levels of linguistic analysis. We should thus speak of syntactic valency and semantic valency. It is shown that semantic valency of nouns with the meaning of integral multitude depends on the degree of concreteness of their meaning. For certain nouns with more abstract meaning semantic valency is obligatory.